AB1006 Anti-Citrullinated Peptide Antibodies and Rheumatoid Factor Testing Patterns among Patients with Rheumatoid Arthritis in The US. (15th July 2016) - An, J.; Lin, A.; Bider, Z.; Alemao, E.; Connolly, S.E.; Cheetham, T.C.
Abstract : Background: Serological markers have been investigated for the identification of RA. Current diagnostic criteria recommend conducting tests for anti-citrullinated peptide antibodies (ACPA) and rheumatoid factor (RF) prior to reaching the RA diagnosis. However, there is a lack of information about how these tests are utilized in a managed care setting. Objectives: To describe the frequency of ACPA/RF tests at the time of RA diagnosis and at follow-up, as well as to compare baseline characteristics between patients who received ACPA/RF tests and those who did not. Methods: A cohort study was conducted using adult patients newly diagnosed with RA within a US integrated healthcare delivery system from 1 January 2007 to 31 December 2014. Individuals were followed from their first RA diagnosis (index date) until 30 June 2015. Patients were required to have two ICD-9 codes of 714.x, treatment with a DMARD, and continuous eligibility for 12 months prior to the index date (baseline period). At baseline, data were collected on co-morbid conditions, laboratory test results and dispensed medications. Descriptive statistics and multivariable logistic regression analyses were conducted to describe ACPA/RF testing patterns and to investigate baseline patient characteristics associated with ACPA/RF testing. Results: A total of 7444 patients with newly diagnosed RA were identified. Mean (SD) age was 55.6 (15.0) years, 75% were female, 69% of patients received corticosteroid treatment and 22% had other autoimmune diseases at baseline. Overall, 83% had both ACPA and RF tests at baseline while 10% and 2% had only an RF or an ACPA test, respectively. Baseline ACPA and RF testing rates were increased over time (p<0.001) and both ACPA and RF testing rates were >90% from 2012 onwards (Table). At baseline, 34% of patients had positive ACPA and RF test results, 30% had negative ACPA and RF results, 6% had only ACPA-positive and 21% had only RF-positive results. During follow-up, 20% of patients repeated their ACPA tests; 11% had a repeat test within 1 year of baseline. Patients with a higher Elixhauser index (odds ratio [OR]=0.72, 95% CI 0.62, 0.95) were less likely to receive ACPA tests at baseline, whereas patients receiving NSAIDs (OR=1.45, 95% CI 1.25, 1.69) or corticosteroids (OR=1.23, 95% CI 1.07, 1.43) were more likely to receive baseline ACPA tests. Patients who had other autoimmune conditions were more likely to repeat their ACPA tests during follow-up. Conclusions: ACPA and RF testing rates in patients with RA have increased over time, with 96% of patients with newly diagnosed RA receiving both tests at the time of RA diagnosis in 2014. However, there may be still discrepancies in testing based on co-morbidities and medications. The reasons why RF or ACPA tests were not conducted in some patients with RA remain to be identified. References: Aletaha D, et al. Ann Rheum Dis 2010;69:1580–8. Disclosure of Interest: J. An Grant/research support from: Bristol-Myers Squibb, A. Lin Employee of: Kaiser Permanente, Z. Bider Employee of: Kaiser Permanente, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. E. Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, T. C. Cheetham Grant/research support from: Bristol-Myers Squibb